Lai Kwan eyes comeback after three-gold show - Lim, Teik Huat (2012)
KUALA LUMPUR: Chui Lai Kwan (pic),once the region's fastest freestyle swimmer, wants to make a comeback forMalaysia in the Myanmar SEA Games next year - provided she can juggle her time between studies and training.